Organizational Commitment as Moderating the Relationship between Professional Commitment, Locus of Control, and Professionalism on Whistleblowing Intention - Vierina Clyde; Imam Abu Hanifah; Munawar Muchlish (AFRE (Accounting and Financial Review), 2022)
The purpose of this study was to determine the effect of organizational commitment as moderating the relationship between professional commitment, locus of control, and professionalism on whistleblowing intention. The population were all 87 Government Internal Supervisory Apparatus (APIP) at the Inspectorate of Banten Province. This study used primary data to obtained important information from the respondents by using purposive sampling method. SmartPLS 3.3.3 was used to analyze the research purpose, that consist are descriptive statistics and hypothesis tested. The result showed that: First, professional commitment has a positive significant relationship toward whistleblowing intention. Second, the locus of control has a positive significant relationship toward whistleblowing intention. Third, professionalism has a  positive significant relationship toward whistleblowing intention. Forth, organizational commitment moderate the relationship between professional commitment toward whistleblowing intention. Fives, organizational commitment moderate the relationship between locus of control toward whistleblowing intention. Six, organizational commitment moderate the relationship between professionalism toward whistleblowing intention.